Analisis Pengelolaan Dana Bantuan Operasional Kesehatan di Puskesmas Kebun Kopi - Syalaisha Anargya Hadi; Dwi Noerjoedianto; Andy Amir; Guspianto Guspianto; Adila Solida (Universitas Malahayati Lampung, 2025)
ABSTRACT The management of Health Operational Assistance funds at Puskesmas is crucial so that budget planning for each program can be carried out as needed. Based on information obtained from the DJPK of the Ministry of Finance (2020), there is a difference between the allocation and realization of the BOK budget in all provinces, with some areas experiencing budget overruns. Puskesmas with the lowest realization of BOK funds in Jambi City are Puskesmas Kebun Kopi and Puskesmas Talang Bakung with the realization of the use of BOK funds only reaching 57%. This study aims to determine how the management of BOK funds at the Kebun Kopi Health Center. This research is a qualitative research with a descriptive approach. The location of this research is at the Kebun Kopi Health Center with a total of 7 informants. In the context aspect, the objectives of the BOK Fund have been aligned with the basic service needs of the community. However, in terms of input, the human resources who manage the funds are not competent. In the process, the main obstacles lie in the delay of technical guidelines, cross-sector coordination, and double workload. In terms of products, the realization of funds is still not optimal. Conclusion: The management of BOK funds at Puskesmas Kebun Kopi still faces challenges in the aspects of human resources, planning, and reporting. Training and strengthening the capacity of managers are needed so that BOK funds can be used more efficiently and on target. Keywords: BOK Fund, Management, Puskesmas, CIPP, Qualitative ABSTRAK Pengelolaan dana Bantuan Operasional Kesehatan di Puskesmas menjadi krusial agar perencanaan anggaran untuk tiap program dapat terlaksana sesuai kebutuhan. Berdasarkan informasi yang diperoleh dari DJPK Kemenkeu (2020), tercatat adanya perbedaan antara alokasi dan realisasi anggaran BOK di seluruh provinsi, dengan beberapa daerah mengalami kelebihan anggaran. Puskesmas dengan realisasi Dana BOK paling rendah di Kota Jambi adalah Puskesmas Kebun Kopi dan Puskesmas Talang Bakung dengan realisasi penggunaan Dana BOK yang hanya mencapai 57%. Penelitian ini bertujuan untuk mengetahui bagaimana pengelolaan dana BOK di Puskesmas Kebun Kopi. Penelitian ini merupakan penelitian kualitatif dengan pendekatan deskriptif. Lokasi penelitian ini di Puskesmas Kebun Kopi dengan jumlah informan sebanyak 7 orang. Pada aspek konteks, tujuan Dana BOK telah selaras dengan kebutuhan pelayanan dasar masyarakat. Namun, dari sisi input, SDM yang mengelola dana tidak sesuai kompetensi. Pada proses, kendala utama terletak pada keterlambatan juknis, koordinasi lintas sektor, serta beban kerja ganda. Dari sisi produk, realisasi dana masih belum optimal. Pengelolaan Dana BOK di Puskesmas Kebun Kopi masih menghadapi tantangan pada aspek SDM, perencanaan, dan pelaporan. Diperlukan pelatihan dan penguatan kapasitas pengelola agar dana BOK dapat digunakan lebih efisien dan tepat sasaran. Kata Kunci: Dana BOK, Pengelolaan, Puskesmas, CIPP, Kualitatif